Carbon Nation : Fossil Fuels in the Making of American Culture - Johnson, Bob (Associate professor) (Book collections on Project MUSE., 2014)
"A close look at our nation's conflicted love affair with fossil fuels (including coal, oil, and natural gas) and their pervasive impact on American life and culture. While carbon has literally fueled a relentless technological progress and provided the highest standard of living the world has ever seen, it's also been the engine for environmental and human degradation, a blithe consumerism unaware of its carbon dependency, and dangerously large concentrations of wealth and power. Focusing on this longstanding contradiction, Johnson argues that our embrace and celebration of carbon has been enabled by distancing ourselves from its costs."--Publisher information.